The Presence and Capabilities of Women on Board and Corporate Financial Performance: a Study on Female vs Maledominated Industry - Permatasari, Widowati Dian; Cahyono, Yuli Tri; Arifin, Atwal (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this study is to determine the effect of the women presence and their capabilities on the companies’ financial performance in company listed on the Indonesia Stock Exchange. This study splits the sample into two industry categories based on gender domination which are female and male-dominated industry. Using agency theory, resourced based theory and human capital theory, this study find that the presence of a women on board has a significant positive impact on the company’s financial performance as measured on market basis. In addition, their capability - such as education background in economics/business/finance and relevant work experience - have significant positive impact on the company’s accounting performance. These results are seen mainly in the entire sample group and the male-dominated sample group.